Diversification of Surimi-Based Processed Products in Meatball Products with Tuna and Mackerel scad Fish Types - Saleh, Mutia Ilham; Talib, Ahmad (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
This research was conducted at the Fishery Product Technology Laboratory of Muhammadiyah University of North Maluku (UMMU) Ternate. In January 2023 with the aim of knowing the effect of adding the concentration of tuna and kite meat to the meatball products produced and the best quality value of tuna and kite meatball products. This study used a completely randomized design, with the types of tests, namely organoleptic test, bite test, folding test. The results showed that tuna meatball products from all test parameters that gave an effect only on the Taste parameter, for the Appearance, Odor and Texture parameters did not give a real effect. While meatball products from fly fish from all tested parameters including Appearance, Odor, Taste and Texture all give a real influence on the quality of the meatballs produced.